Aktivitas Media Relations Humas Setda Kota Salatiga dalam Membentuk Berita Positif - Nugrahaning Esa Pratiwi; Richard Gordon Mayopu; George Nicholas Huwae (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
This research aims to find out the role of media relations in forming positive news on printed media by having a special page for Salatiga news as research focus. This research is a qualitative research by using qualitative descriptive approach. Observation, interview, document collection and photo activities are used to collect data. The result indicates that informal media relations activities are more effective to create positive news about Salatiga government in printed media because it can build good relation between Public Relations practitioners and journalists.